Innovation and Technological Adaptation of Business Actors in the Digital Age: A Digital Sociology Perspective - Ambo Upe (CV. Literasi Indonesia, 2023)
The advancement of information technology has changed many aspects of human life. Technology has entered various spaces of human life, so technology and humans are an integral unit. In the modern economic sector, the market has transformed business digitalization. This is both a challenge and an opportunity for business people. For this reason, this study aims to analyze the space for innovation and technological adaptation of business actors in responding to advances in information technology. In addition, this research also intends to outline the relevance of developing digital sociology studies. A qualitative approach through field studies and literature review is the method of choice for this research. Operationally, the research was conducted through two stages, namely the context determination stage and the concept selection stage. These two processes are in line with the principle of inductive logic in qualitative research which prioritizes empirical narratives and then develops conceptual narratives. This is intended to obtain a comprehensive understanding of the facts and theories about technological innovation and adaptation in the business world. The results show that digital technology has become a major catalyst for improving operational efficiency, expanding market reach, and creating competitive differentiation. Therefore, digital technology adaptation is not just an option but has become a necessity in an increasingly digitally connected era. Digital technology adaptation is one of the keys to success in a world that is undergoing a massive transformation from real space to digital space.